THE IMPLEMENTATION OF THE SUBSIDIZED CHEAP FOOD DISTRIBUTION POLICY IN THE CITY OF SOUTH JAKARTA - Kurniati, Poni Sukaesih; Paliama, Silvia Cesilia (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This study aims to see the success of implementing the subsidized cheap food distribution policy in the City of South Jakarta. This research adopts a qualitative descriptive method, which involves depicting and analyzing data collected based on the conditions of implementing the subsidized cheap food distribution policy in South Jakarta. The data sources are obtained through secondary data. The data collection is conducted using a literature study. The study shows that the Jakarta City Government has successfully implemented the subsidized cheap food distribution policy, and the people of South Jakarta have accepted it. The impact of implementing the subsidized cheap food distribution policy in South Jakarta is the effort to provide food security to the community, especially in South Jakarta, due to the increase in poverty caused by COVID-19.